2017
DOI: 10.1111/jpn.12808
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and morphological changes in the intestinal mucosa associated with increased permeability induced by short‐term fasting in chickens

Abstract: Short-term fasting for 4.5 and 9 hr has been demonstrated to increase intestinal permeability (IP) in chickens. This study aimed to investigate the effects of 0, 4.5, 9 and 19.5 hr fasting on intestinal gene expression and villus-crypt architecture of enterocytes in jejunal and ileal samples. On day 38, Ross-308 male birds were fasted according to their group and then euthanised. Two separate intestinal sections (each 2 cm long, jejunum and ileum) were collected. One section was utilised for villus height and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 49 publications
8
38
1
Order By: Relevance
“…In addition, the expression of the anti-inflammatory cytokine TGF-β4, and that of HSP-70 included in tissue protection and repair were not affected by the short-term fasting. This is in agreement with Gilani et al [30], who showed the absence of changes in HSP-70 gene expression in the jejunum and ileum of up to 19.5 h fasted chickens. Taken together with these results, it seems that feed withdrawal for 15.5 h induced an intestinal inflammatory response through TLR4 signaling.…”
Section: Effect Of Fasting Periodsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, the expression of the anti-inflammatory cytokine TGF-β4, and that of HSP-70 included in tissue protection and repair were not affected by the short-term fasting. This is in agreement with Gilani et al [30], who showed the absence of changes in HSP-70 gene expression in the jejunum and ileum of up to 19.5 h fasted chickens. Taken together with these results, it seems that feed withdrawal for 15.5 h induced an intestinal inflammatory response through TLR4 signaling.…”
Section: Effect Of Fasting Periodsupporting
confidence: 93%
“…On the other hand, fasting period significantly reduced FABP6 expression in the ileum, corroborating results showed by Gilani et al [30]. This protein is involved in bile acid transport across the epithelium, and, according to Gilani et al [30], FABP6 downregulation in fasted birds might indicate a reduced bile acid production as a consequence of dietary fatty acid absence. Furthermore, considering the described effect of several dietary components (e.g., glutamine, fatty acids) and bacteria on claudin expression [37], it seems plausible that the lack of nutrients during fasting might affect Claudin-1 expression and increase permeability.…”
Section: Effect Of Fasting Periodsupporting
confidence: 84%
See 2 more Smart Citations
“…Barrier function is often determined by tight junction integrity of epithelial layers because tight junction plays an important role in sealing the apical gaps [33]. The decreased expression of tight junction-related genes and proteins has been considered a molecular evidence for impaired barrier functions [34]. Therefore, we measured selected tight junction-related protein expression in the trachea mucosa.…”
Section: Discussionmentioning
confidence: 99%